1985
DOI: 10.1159/000128445
|View full text |Cite
|
Sign up to set email alerts
|

Variations in Transmucosal Gastric Potential Difference during Hemorrhagic Shock in the Rat

Abstract: Transmucosal gastric potential difference (TGPD) was measured in the antrum and fundus of the stomach in two groups of rats submitted to hemorrhagic shock. In the first group the stomach contained 2 cm3 of 0.1 N HCl and in the second 2 cm3 of physiological saline. After the hemorrhage both antral and fundal TGPD diminished significantly in both groups. Antral TGPD dropped from –20 to –6 mV (p < 0.001) in the first group and from –22 to –12 mV (p < 0.01) in the second group; fundal TGPD dr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

1986
1986
1995
1995

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 3 publications
0
4
0
Order By: Relevance
“…In fact, in a previous experiment we demonstrated that GTPD always falls during hemorrhage, but it gradually returns to basal values after rein fusion of the shed blood if no anatomical damage of the mucosal barrier has occurred. On the contrary, the postreinfusion GTPD does not recover in the presence of anatomi cal mucosal lesions [12]. Therefore, the smaller difference between basal and final GTPD values in rats treated with cold gas tric infusion reflects less severe mucosal damage.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…In fact, in a previous experiment we demonstrated that GTPD always falls during hemorrhage, but it gradually returns to basal values after rein fusion of the shed blood if no anatomical damage of the mucosal barrier has occurred. On the contrary, the postreinfusion GTPD does not recover in the presence of anatomi cal mucosal lesions [12]. Therefore, the smaller difference between basal and final GTPD values in rats treated with cold gas tric infusion reflects less severe mucosal damage.…”
Section: Discussionmentioning
confidence: 95%
“…Since it is commonly accepted that mucosal isch emia plays an important role in the patho genesis of gastric stress lesions [6,8,12], cooling appears to have contrasting effects on the ischemic gastric mucosa. It is well known that cooling reduces the energetic re quirements of tissues, lessening the ischemic damage but, on the other hand, gastric cool ing reduces the mucosal blood flow, aggrav ating the gastric ischemia [5,9], Therefore it seems important to assess the overall effect of cold and warm gastric irrigation during hemorrhagic shock in rats by evaluating the degree of gastric ulceration and the behavior of gastric transmucosal potential difference (GTPD), which is a very sensitive index of anatomical and functional alterations of the gastric mucosa [1,10,12].…”
Section: Introductionmentioning
confidence: 99%
“…Since the active transport of sodi um is relatively fast compared with the passive diffusion of chloride ions, the net result is a greater number of posi tive charges on the serosal surface and a greater number of negative charges on the luminal surface. Further, since epithelial types inherently differ with respect to rate and type of ions transported and/or the magnitude and type of epithelial resistance to passive ion movements, each tis sue has its own characteristic PD [10], PD originates through an energy-requiring process and has been shown to decline when oxygen availability is reduced [11][12][13][14],…”
Section: Origin Of Pdmentioning
confidence: 99%
“…The luminal surface of the gastric mucosa is electrically negative when compared with the serosal surface [1], There is a prominent lumen-negative transmucosal potential dif ference in the stomach (gastric potential dif ference, GPD) [2], Even if different ions are implicated in the generation of GPD, its principal source seems to be the active transport of chloride ions from the intracellular space against both concentration and electrochemical gradients [2,3], GPD originates through an energyrequiring process and has been shown to decline when oxygen availability is reduced [4][5][6][7][8].…”
Section: Introductionmentioning
confidence: 99%